The Impact of Leadership Styles on Employee Performance in the Insurance Industry: A Case Study on Jubilee Life Insurance - Keisha Kego Arago (Uganda Christian University, 2024)
The study's goal was to investigate how leadership philosophies affect workers' performance in Uganda's Jubilee Life Insurance Company. Examining the impact of authoritarian, supporting, and democratic leadership styles on worker performance, as well as the effects of democratic leadership on worker performance, were the specific goals of this study. The literature review, which was included in chapter two, included papers from different academics to further our investigation. This chapter provided an outline of the key ideas and then went on to discuss more of the specific goals, providing further detail to support the effort and expand the goals of the research. The approach for the research is presented in Chapter three. It includes the research design, in which the researcher used a quantitative approach; the study population was 90, and the sample size was 56; the researcher used a questionnaire as the data collection tool, asking respondents to fill it out with as much primary data as possible; the data quality, which includes validity and reliability; and the methods of data presentation In Chapter four, the researcher analyzed the results for each of the objectives using the previously specified sample size. The researcher also went on to interpret the results from Jubilee Insurance Company, providing the study findings in relation to the objectives. Lastly, Chapter five which is the last chapter summarized data in a more precise way. In addition, it provided the recommendations and conclusions of the study.
Undergraduate research